KEDUDUKAN ANAK ANGKAT PEREMPUAN TERHADAP HARTA WARISAN DI KALANGAN ETNIS TIONGHOA DI KOTA MEDAN - EDY MAYOR (PREMISE LAW JURNAL, 2015)
Chinese ethnic group has matrilineal system which means that only the boy who has the right to inherit his parents' wealth. . But, based on the result of the research, inheritance is not only given to the boys but also to the girls which indicates that there has been the shift of understanding about their custom. The research used descriptive analytic method. The data were gathered by using library research and field research. Chinese Hainan ethnic group in Medan usually adopt children by using customary method because of their lack of knowledge of legal system on adoption in Indonesia, and there is a legal loophole in implementing the regulations practically so that there is the potential legal conflict in the future. Besides that, in Chinese Hainan ethic group in Medan there is the shift of custom in the inheritance system from matrilineal to bilateral hereditary line. Keywords: Chinese Hainan Ethnic Group in Meda